Inclusive Sexual Education: Integrating Gender Approaches in Learning - Suwarni Suwarni; Suud Sarim Karimullah; Kaniah Kaniah; Tri Amanat; Muh. Safar; Indra Tjahyadi (STAI Hubbulwathan Duri, 2024)
The importance of integrating gender approaches into inclusive sexuality education is prominent in creating a safe, supportive educational environment as well as providing a holistic understanding of sexual and gender issues. This study aims to investigate the positive impact of integrating gender approaches in inclusive sexuality education on individual knowledge of gender issues, gender awareness and sexual behavior. The library research method is the main framework to explain the theoretical foundations and previous findings in this area, identify potential research gaps, and formulate a solid framework for this topic. The results showed that sex education that pays attention to gender issues has a positive impact on increasing understanding of gender roles in relationships and sexuality, reducing negative gender stereotypes, and creating an inclusive learning environment. In addition, gender awareness plays an important role in shaping attitudes that are supportive of gender diversity and sexual orientation, which in turn promotes healthy sexual behavior and open communication in relationships. Evaluating the effectiveness of sex education programs that incorporate gender issues has also proven to be very important in improving the quality of such programs. Inclusive and gender-sensitive sexuality education thus serves not only to increase understanding but also as a tool for building a more inclusive society, respecting gender diversity and promoting safe and healthy sexual behavior.